Evaluation of non-target animal exposure to human adenovirus recombinant oral rabies vaccine - Ohio 2012 - Wallace, R.; Blanton, J.; Vora, N.; Dyer, J.; Smith, K.; Chipman, R.; Rupprecht, C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Oral Rabies Vaccination (ORV) is the primary management practice for controlling wildlife rabies in the United States, particularly among raccoons and foxes. Two ORV bait designs are primarily utilized for the distribution of vaccinia rabies glycoprotein (VRG) vaccine: a fish meal polymer block and a coated sachet. A primary public health concern related to ORV bait distribution is non-target contact between the ORV and humans and domestic pets. The VRG virus strain used in ORV is attenuated in mice, but human percutaneous exposure to ruptured sachets has resulted in localized vaccinia virus infection in very rare cases. Recently, a new recombinant human adenovirus ORV (AdRG) has been developed. This vaccine is incorporated in ultralight bait which has not previously been used in the United States. Surveillance for human contact is important, particularly among young children that may have contact with the bait, due to their lower prevalence of prior exposure and immunity to human adenoviruses. To evaluate potential differences in contact rates between the VRG and AdRG bait types CDC, the Ohio Department of Health, and USDA/WS will conduct an investigation during ORV baiting in Northeastern Ohio in August 2012. The focus of this investigation will be to ensure that public health programs are in place to capture events of human and domestic animal bait contact, ensure appropriate protocols are in place in case of a severe adverse event from a bait contact, and evaluate whether the AdRG vaccine bait matrix is associated with a different human detection rate compared to bait types used for distributing VRG. Updated guidelines related to appropriate management of potential contacts with AdRG baits during ORV activities may be developed based on findings from this investigation.